Colorado Kid - King, Stephen (New York : Dorchester Pub., 2005)
A rookie newspaperwoman learns the true meaning of mystery when she investigates a twenty-five-year-old unsolved and very strange case involving a dead man found on an island off the coast of Maine.
87562
Keywords: Homicide investigation -- Maine -- Fiction; Missing persons -- Investigation -- Maine -- Fiction; Newspaper employees -- Fiction; Forensic sciences -- Fiction; Mystery fiction